Paleoseismic Investigations along the Bubu Fault, Dodoma-Tanzania - Macheyeki, AS; Delvaux, D; Batist, MD; Mruma, A (Tanzania Journal of Science, 2021)
The central part of Tanzania, Dodoma, was hit by an Mw= 5.5 earthquake in November 4, 2002. It was part of a swarm of moderate earthquakes that affected the area. This paper, reports the first attempt to investigate significant past earthquakes along one of the known seismically active rift faults (Bubu fault, Gonga segment) by paleoseimological trenching. The trench revealed over 3 episodes of faulting (2 of which correspond to Mid-Holocene faulting). The magnitude of the largest earthquake illustrated in the trench is estimated at Mw = 6.3-6.4 and the slip rate between two recent faulting events is about 0.11 to 0.12 mm / yr. This shows that the Gonga segment of the Bubu fault is moderately tectonically active but seismically active of magnitudes of higher magnitudes. Key words: Tanzania, Dodoma, Bubu fault, paleoseismic investigation, earthquake magnitude, slip rate, faulting